PANDANGAN ERA TRANSISI PENGELOLAAN SAMPAH DI INDONESIA: DARI BERBASIS MASYARAKAT MENUJU WASTE TO ENERGY: Indonesia - Iresha, Fajri Mulya; Gutama, Hatta; Rizkianto, Febrian (Teknik Lingkungan Universitas Islam Indonesia, 2026)
Indonesia has experienced a significant period of community-based waste management that has gained global recognition. Initiatives such as waste banks, 3R waste processing facilities (TPS 3R), waste donation programs, and creative communities such as Pandawara Group reflect the strength of public participation in addressing waste-related challenges. However, these approaches have begun to reveal their limitations, as they are often sporadic, unsystematic, and insufficient to address structural issues, including inadequate waste management services, institutional dualism between regulators and operators, and limited local government financing. Indonesia is currently facing emerging challenges, such as overcapacity at final disposal sites (TPAs), landfill fires, leachate pollution, and increasing waste generation driven by rapid urbanization. This article aims to analyze the transition of waste management in Indonesia from a community-based approach toward a modern system that incorporates Waste-to-Energy (WtE) technology. The study was conducted through a literature review and policy analysis of waste management practices implemented across various regions. The findings indicate that the success of this transition depends not only on technological and infrastructural readiness but also on the integration of formal waste management systems with community participation at the grassroots level. Future waste management models in Indonesia should position communities as strategic partners within the WtE framework in order to achieve waste management that is equitable, efficient, and sustainable.